Riscos hidrometeorológicos híbridos na bacia do Alto Iguaçu – Paraná (Brasil) - Gabriela Goudard; Francisco de Assis Mendonça (Confins)
Understanding the risks related to the climate is highly complex, making it necessary to understand the conditions of danger, susceptibility and vulnerability in a combined approach. In this context, the present article highlights an analysis of hybrid risks related to extreme rainfall episodes (floods) in the Alto Iguaçu basin. For that, data from areas of flooding, susceptibility and vulnerability are used, which are analyzed in an integrated perspective. The main results highlight the following points: I) the hybrid risk is the result of a combination of social, natural and technological factors in the environment; II) hybrid hydrometeorological risks are differentiated along the basin, with overlaps between areas of high to very high vulnerability and the portions most affected by extreme rain episodes and; III) the hybrid risk analysis proposal is configured as an attempt at systemic and holistic analysis, aiming at risk management.